Growth Kinetics of Attached Iron-Oxidizing Bacteria - Wichlacz, Paul L. (1985)
A model of growth and substrate utilization for ferrous-iron-oxidizing bacteria attached to the disks of a rotating biological contactor was developed and tested. The model describes attached bacterial growth as a saturation function in which the rate of substrate utilization is determined by a maximum substrate oxidation rate constant (P), a half-saturation constant (K(s)), and the concentration of substrate within the rotating biological contactor (S(1)). The maximum oxidation rate constant was proportional to flow rate, and the substrate concentration in the reactor varied with influent substrate concentration (S(0)). The model allowed the prediction of metabolic constants and included terms for both constant and growth-rate-dependent maintenance energies. Estimates for metabolic constants of the attached population of acidophilic, chemolithotrophic, iron-oxidizing bacteria limited by ferrous iron were: maximum specific growth rate (μ(max)), 1.14 h(−1); half-saturation constant (K(s)) for ferrous iron, 54.9 mg/liter; constant maintenance energy coefficient (m(1)), 0.154 h(−1); growth-rate-dependent maintenance energy coefficient (m′), 0.07 h(−1); maximum yield (Y(g)), 0.063 mg of organic nitrogen per mg of Fe(II) oxidized.